College student insomnia: The influence of insomnia on emotional aggression - Chintya, Sheldya Kayla; Chairi, Najwa Putri; Rahmawati, Yuliana Mukti (Flourishing Journal, 2025)
Poor sleep quality, particularly insomnia, can affect emotional regulation and increase emotional aggression. This study aims to investigate the relationship between insomnia symptoms and emotional aggression in university students. This study employed a quantitative approach, adapting the Regensburg Insomnia Scale (RIS) to assess student insomnia and the Brief Aggression Questionnaire (BAQ) to measure emotional aggression. Both instruments use Cronbach’s alpha for reliability and construct validity. This study involved 69 college students with sleeping problems, selected using a convenience sampling technique. Data were collected using an online questionnaire via Google Forms. Data analysis used correlational statistical methods to explore the role of insomnia to emotional aggression. This study found a significant contribution of insomnia to emotional aggression in college students. The results of the analysis show that the higher a person's level of insomnia, the higher the level of emotional aggression. These findings are expected to provide a further understanding of the impact of insomnia on the emotional aggression of university students, as well as a reference for the development of intervention strategies to improve sleep quality and reduce emotional aggression among university students. AbstrakKualitas tidur yang buruk, terutama insomnia, dapat memengaruhi regulasi emosi dan meningkatkan agresi emosional. Penelitian ini bertujuan untuk menyelidiki hubungan antara gejala insomnia dan agresi emosional pada mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif dan mengadaptasi Regensburg Insomnia Scale (RIS) yang mengukur insomnia dan Brief Aggression Questionnaire (BAQ) mengukur agresi emosi. Kedua alat ukur tersebut menggunakan reliabilitas Cronbach alfa dan validitas konstruk. Penelitian ini melibatkan 69 mahasiswa yang memiliki masalah tidur, yang dipilih dengan menggunakan teknik convenience sampling. Data dikumpulkan dengan menggunakan kuesioner online melalui Google Forms. Analisis data menggunakan metode statistik korelasional untuk mengeksplorasi peran gejala insomnia terhadap agresi emosional. Hasil dari penelitian ini menemukan adanya peran yang signifikan gejala insomnia terhadap agresi emosi mahasiswa. Individu yang memiliki tingkat insomnia yang tinggi memiliki tingkat agresi emosi yang tinggi pula. Temuan ini diharapkan dapat memberikan pemahaman lebih lanjut mengenai dampak insomnia terhadap agresi emosional mahasiswa, serta menjadi acuan pengembangan strategi intervensi untuk meningkatkan kualitas tidur dan menurunkan agresi emosional di kalangan mahasiswa.